2013
DOI: 10.1108/10610421311298650
|View full text |Cite
|
Sign up to set email alerts
|

Exploring branding strategies of FMCG, services and durables brands: evidence from India

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Previous studies have reported differences in marketing communications between services, FMCG and durables (Dibb and Simkin, 1993;Stafford, 1996;Pina et al, 2006; 22 MIP 34,1 Mann and Kaur, 2013;Tripp, 1997). The following four characteristics discussed in the context of IMC are largely accepted in the literature as differentiating services from products (Dibb and Simkin, 1993;Parasuraman et al, 1985).…”
Section: Implications Of the Characteristics Of Services For Marketin...mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported differences in marketing communications between services, FMCG and durables (Dibb and Simkin, 1993;Stafford, 1996;Pina et al, 2006; 22 MIP 34,1 Mann and Kaur, 2013;Tripp, 1997). The following four characteristics discussed in the context of IMC are largely accepted in the literature as differentiating services from products (Dibb and Simkin, 1993;Parasuraman et al, 1985).…”
Section: Implications Of the Characteristics Of Services For Marketin...mentioning
confidence: 99%
“…Services tend to be heterogeneous in quality (Dibb and Simkin, 1993) due to minimal tangible differentiation. As a consequence, services rely more on a corporate brand while FMCG rely more on a house of brands approach (Mann and Kaur, 2013). Firms seek to overcome the greater perception of risk associated with services by focusing on a strong corporate brand (De Chernatony and Dall'Olmo Riley, 1999;Berry, 2000;McDonald et al, 2001).…”
Section: Implications Of the Characteristics Of Services For Marketin...mentioning
confidence: 99%
See 1 more Smart Citation
“…As introduced above, PL brands typically operate under umbrella brands, meaning a product brand operates under the same name as the corporate brand or the store brand, thereby creating a connection between the umbrella brand and a product brand (Keller et al, 2020;Morrin, 1999). In fast-moving consumer goods (FMCGs) sector, companies seldom use single corporate brands, but instead, corporate brands are used as endorsers for product brands (Jit Singh Mann and Kaur, 2013). PL brands can vary from economy PL brands to standard PL brands to premium PL brands.…”
Section: Multiple-tier Private Label Brand Portfolio Architecturementioning
confidence: 99%
“…Food products which are targeted for export to the MENA region are categorised as fast moving consumer goods (FMCG) or popularly known as consumer packaged goods (CPG) (Selvakumar, 2013;Malhotra, 2014). FMCG products are goods which are frequently purchased, have low consumer engagement, low risk and a relatively low cost of purchase (East, 1997;Kotler, 2000;Mann & Kaur, 2013). Hence, the packaging aspect plays a role as the main marketing function due to the nature of the commodity which is extremely competitive (Rambabu & Porika, 2020).…”
Section: Introductionmentioning
confidence: 99%